2015
DOI: 10.4103/0972-3919.147530
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m dimercaptosuccinic acid scan in evaluation of renal cortical scarring: Is it mandatory to do single photon emission computerized tomography?

Abstract: Objectives:Renal cortical scintigraphy with technetium-99m (Tc-99m) dimercaptosuccinic acid (DMSA) is the method of choice to detect acute pyelonephritis and cortical scarring. Different acquisition methods have been used: Planar parallel-hole or pinhole collimation and single photon emission tomography (SPECT). This study compared planar parallel-hole cortical scintigraphy and dual-head SPECT for detection of cortical defects.Patients and Methods:We retrospectively reviewed 190 consecutive patients with 380 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies have searched for incremental values of DMSA SPECT in addition to planar imaging, mainly among patients with suspected pyelonephritis or cortical scarring following infection [ 15 16 17 ]. Although the results are not directly applicable to patients with renal injuries for which the grades of cortical damages vary to a wider extent, differences in SRF between planar and SPECT have been reported, similar to our observation: Reichkendler et al [ 12 ] showed a mean bias of 2.1%, which increased in kidneys with SRF beyond the normal range (SRF difference > 10%); a negative correlation between the difference and mean of SRF values on Bland-Altman plot was described by Cao et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have searched for incremental values of DMSA SPECT in addition to planar imaging, mainly among patients with suspected pyelonephritis or cortical scarring following infection [ 15 16 17 ]. Although the results are not directly applicable to patients with renal injuries for which the grades of cortical damages vary to a wider extent, differences in SRF between planar and SPECT have been reported, similar to our observation: Reichkendler et al [ 12 ] showed a mean bias of 2.1%, which increased in kidneys with SRF beyond the normal range (SRF difference > 10%); a negative correlation between the difference and mean of SRF values on Bland-Altman plot was described by Cao et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cortical imaging with 99m Tc-DMSA is the gold standard for renal cortical scarring imaging. Gamma radiation, appropriate half-life, availability of 99m Tc made, 99m Tc-DMSA is a radiopharmaceutical commonly used to detect renal scarring or acute pyelonephritis and provide accurate differential renal function ( Saleh Farghaly and Mohamed Sayed, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, because SPECT has to obtain information of kidney from every angle and recompose images, test time requirement is naturally long, so it is not clinically useful for unconscious patients or pediatric patients. The clinical effectiveness of kidney SPECT has not been much studied yet, but it was reported that SPECT has increased sensitivity to kidney cortex defect [10][11][12][13]. Therefore, the present study 18.5-22.9 were selected.…”
mentioning
confidence: 99%